TRANSACTION COSTS IN INDONESIA STOCK MARKET: A STUDY IN THE AUTOMATION PERIOD - Mamduh M. Hanafi (University of Merdeka Malang, 2015)
We studied transaction costs in Indonesia market extended closely by Bonser-Neal et al. (1999). They investigatedtransaction costs in Jakarta Stock Exchange (JSX) using period before automation (May 1995). To matchclosely with Bonser-Neal et al. (1999), we used period right after JSX introduced trading automation (JATS orJakarta Automated Trading System). We used period from May 1995 to March 2003. We found that transactioncosts in the automation period were larger than those reported by Bonser-Neal et al. (1999). Automationdid not seem to automatically reduce transaction costs as expected. We found that domestic investors had largerprice impact than foreign investors. Similar to previous finding, we found that trade difficulty had a positiveeffect on price impacts. We also found transaction costs in crisis period were larger than those in normal period.We also found that size had a negative relationship with price impacts. Our paper provided evidence of thetransaction costs in Indonesia market after the automated trading was introduced in Indonesia market.